The Impact of Metabolic Syndrome on Immune Regulation (IL-17, IL-23, and FOXP3+), Psoriasis Severity, Flare Frequency, and Quality of Life in Psoriasis Patients: A Cross-Sectional Study - Flora Ramona Sigit Prakoeswa; Faradiba Maharani; Saiful Hidayat; Winda Atika Sari; Triasari Oktavriana; Cita Rosita Sigit Prakoeswa; Menul Ayu Umborowati; Ratih Pramuningtyas; Rochmadina Suci Bestari; Riandini Aisyah; Erika Diana Risanti; Listiana Masyita Dewi; et al. (International Journal of Inflammation)
Conclusions: MetS is associated with immune dysregulation, evidenced by reduced FOXP3+ expression in psoriasis patients. Further studies are needed to explore the immunological link between psoriasis and MetS.